Application of MRI and CT Images in Surgical Treatment of Early Cervical Cancer. (2nd August 2022) - Lu, An; Lu, Guohua
Abstract : In order to understand the problems of the application of MRI and CT images in the early cervical cancer surgery, a method that the application of MRI imaging and CT images in early cervical cancer surgery was proposed. For the cervical cancer in clinical practice, the applications of the modern imaging examination and the clinical staging classification were investigated and analyzed. Compared with the surgical pathology results, the application value of common modern imaging in clinical staging of cervical cancer was evaluated. It was found that the sensitivity of MRI and CT in diagnosing lymph node metastasis was 56% and 58%, and the specificity was 93% and 92%, respectively. The experiment proved the application value of MRI and CT in clinical staging of cervical cancer.